1993
DOI: 10.1007/bf00341318
|View full text |Cite
|
Sign up to set email alerts
|

Competition between an introduced and an indigenous species: the case of Paspalum paspalodes (Michx) Schribner and Aeluropus littoralis (Gouan) in the Camargue (southern France)

Abstract: Paspalum paspalodes, an introduced grass species, and Aeluropus littoralis, an indigenous species, develop abundantly in seasonally-flooded marshes in the Camargue (Rhône Delta, France). Although they occur together in many multispecies communities, neither species occurs when the other is dominat. The cultivation of cuttings of P. paspalodes and A. littoralis in a replacement series in a combination of five proportions (0/100, 25/75, 50/50, 75/25 and 100/0) and four salinities (0,2 4, and 6 g Cl · 1) gave con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…P. distichum, an introduced grass from Asia, was the dominant perennial of the shallow-marsh and the second most abundant species at the site during the study. In its native freshwater Indian wetlands it is reported from a wide MWL range (1-89 cm) (Middleton et al 1991) but is sensitive to salinity; Meslé ard et al (1993) reported a reduction in mean yield at salinities of 3.1 mS/cm and absence at salinities of 6 mS/cm. It is likely that the grassland assemblage water regime meets the hydrological needs of P. distichum while avoiding salinity and represent a salinity 'refuge'.…”
Section: Shallow Brackish Marshmentioning
confidence: 98%
“…P. distichum, an introduced grass from Asia, was the dominant perennial of the shallow-marsh and the second most abundant species at the site during the study. In its native freshwater Indian wetlands it is reported from a wide MWL range (1-89 cm) (Middleton et al 1991) but is sensitive to salinity; Meslé ard et al (1993) reported a reduction in mean yield at salinities of 3.1 mS/cm and absence at salinities of 6 mS/cm. It is likely that the grassland assemblage water regime meets the hydrological needs of P. distichum while avoiding salinity and represent a salinity 'refuge'.…”
Section: Shallow Brackish Marshmentioning
confidence: 98%
“…However, its role in early establishment success at the local scale may be limited compared with the effect of differences in fitness (Funk & Wolf, ; Kunstler et al, ). Fitness advantage can arise from greater ability to effectively use resources in a specific range of environmental conditions (Freckleton & Watkinson, ; Keddy & Shipley, ; Mesléard, Ham, Boy, van Wijck, & Grillas, ), resulting in a competitive hierarchy (Fargione et al, ; Herben & Goldberg, ). Competitive hierarchies have been shown to occur within functional groups (Turnbull, Coomes, Hector, & Rees, ; Turnbull et al, ; Wedin & Tilman, ), contrary to the within‐group equivalence predicted by limiting similarity (Hubbell, ).…”
Section: Applications Of Limiting Similarity Involve Oversimplificationmentioning
confidence: 99%
“…Aeluropus littoralis is a perennial monocot grass with the small haploid genome of 349 Mb (2n = 2X = 14) using the C 4 mechanism for carbon fixation [2] that grows in dry salty areas or marshes [3]. Aeluropus littoralis can survive where the water salinity is periodically high [4] and tolerate up to 1100 mM sodium chloride [5]. Therefore, A. littoralis can serve as valuable genetic resource for understanding the molecular mechanisms of stress-responses in monocots, and can potentially be used for improving tolerance to abiotic stresses in economically important crops [6].…”
Section: Introductionmentioning
confidence: 99%